Domain-selective BET inhibition attenuates transcriptional and behavioral responses to cocaine. (1st June 2022) - Singh, Mandakini B.; Babigian, Christopher J.; Sartor, Gregory C.
Abstract: Epigenetic pharmacotherapies have emerged as a promising treatment option for substance use disorder (SUD) due to their ability to reverse maladaptive transcriptional and behavioral responses to drugs of abuse. In particular, inhibitors of bromodomain and extra terminal domain (BET) reader proteins have been shown to reduce cocaine- and opioid-seeking behaviors in rodents. However, only pan-BET inhibitors, small molecules that bind to both bromodomains (BD1 and BD2) with all BET proteins, have been investigated in animal models of SUD. Given the potential side effects associated with pan-BET inhibitors, safer and more selective strategies are needed to advance BET therapeutics as a potential treatment for SUD. Here, we show that RVX-208, a clinically tested, BD2-selective BET inhibitor, dose-dependently reduced cocaine conditioned place preference in male and female mice, similar to the pan-BET inhibitor JQ1. In other behavioral experiments, RVX-208 treatment did not alter distance traveled, anxiety-like behavior, or novel object recognition memory. At the transcriptional level, RVX-208 attenuated the expression of multiple cocaine-induced genes in the nucleus accumbens in a sex-dependent manner. RVX-208 produced a distinct transcriptional response in stimulated primary neurons compared to JQ1 but had little effect on gene expression in non-stimulated neurons. Together, these data indicate that targeting domain-specific BET mechanisms may be an effective and safer strategy to reduce cocaine-induced neurobehavioral adaptations. Graphical abstract: Image 1 Highlights: RVX-208 is a clinically tested BD2-selective BET inhibitor with limited side effects. RVX-208 reduced cocaine conditioned responding without affecting other behaviors. RVX-208 attenuated cocaine-induced gene expression in the nucleus accumbens. In primary neurons, RVX-208 produced a unique transcriptional profile compared to JQ1.